Coming of age in Mississippi : the classic autobiography of growing up poor and black in the rural south - Moody, Anne (A Dell book, 1976)
Amy Moody shares her experiences growing up in the rural South in the 1940s and 50s, and explains how she became involved in the civil rights movement. A deeply personal story but also a portrait of a turning point in our nation's destiny, this autobiography lets us see history in the making, through the eyes of one of the foot soldiers in the civil rights movement.